An optimal method of assessment the individual susceptibility to noise-induced hearing loss - DUDAREWICZ, Adam; PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata; ŚLIWIŃSKA-KOWALSKA, Mariola (Archives of Acoustics, 2007)
The aim of the investigation was to compare different methods of subject classification regarding susceptibility to noise induced hearing loss in group of 949 workers of power plant. In the first two methods, simple and accurate the classification was performed according international reference standard ISO 1999:1990. In the tree other methods the entire group of workers was divided into subgroups to obtain similar distribution of age, time of employment and level of noise exposure in the susceptible and resistant group. In the first two classifications the susceptible group was significantly younger then resistant group, had shorter time of employment and lower level of noise exposure. This findings are in line with the definition of increased vulnerability to noise inducted hearing loss. Additionally, an excellent separation between hearing thresholds (HTs) of the susceptible and the resistant group was achieved. All three other methods resulted in worse separation of HTs between susceptible and resistant group of subjects. Subjects pre-selection deteriorates the reliability of workers’ dichotomization into noise-susceptible and noise resistant groups.